Joint operating agreement: applicability and enforceability of default provisions - Pereira, Eduardo G. (Rocky Mountain Mineral Law Foundation, USA, 2018)
-Analysis and comparison of various international JOA model forms -Obstacles to enforcement of default remedies in civil law jurisdictions -Operator as defaulting party -Impact of governing law and dispute resolution clauses Effect of insolvency -National oil company participation -Enforceability of forfeiture and buy-out provisions under -English law after Makdessi -Sole risk, non-consent, and mutatis mutandis -Unitization and unit operating agreements -Accounting procedures